2018
DOI: 10.1186/s12883-018-1090-8
|View full text |Cite
|
Sign up to set email alerts
|

Environmental exposures and the risk of multiple sclerosis in Saudi Arabia

Abstract: BackgroundMultiple sclerosis (MS) is the most common non-traumatic condition that leads to disability among young individuals. It is associated with demyelination, inflammation, and neurodegeneration within the central nervous system. Information on risk factors of multiple sclerosis is crucial for the prevention and control of the disease. The aim of this study was to determine risk factors of MS among adults in Saudi Arabia.MethodsA matched multicenter case-control study, including 307 MS patients and 307 he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 31 publications
3
30
0
Order By: Relevance
“…The socio-demographic and clinical findings of the study revealed that the majority of MS patients were female versus male with Mean ±SD (30.24 ± 12.8), these findings are generally consistent with [21] who reported that 78% of MS patients were female and 22% were male at the peak age is between 20 and 30 years, as well as [22] who stated that MS usually affects women rather than men, between 20 and 40 years and in their most productive years of life. Moreover, [23] mentioned that MS is usually diagnosed in young adults and affects women two to three times as often as men.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The socio-demographic and clinical findings of the study revealed that the majority of MS patients were female versus male with Mean ±SD (30.24 ± 12.8), these findings are generally consistent with [21] who reported that 78% of MS patients were female and 22% were male at the peak age is between 20 and 30 years, as well as [22] who stated that MS usually affects women rather than men, between 20 and 40 years and in their most productive years of life. Moreover, [23] mentioned that MS is usually diagnosed in young adults and affects women two to three times as often as men.…”
Section: Discussionsupporting
confidence: 86%
“…The researchers believes that fatigue in MS increase and worsens with the age as result of its progressive disease course and early self-management strategies on early MS stage in young adult can helps in maintaining good Quality of life and prevent later complications or disability in MS patients. The study result in consistent with [44,45] who explained that age was a significant factor influencing fatigue and strongest predictor of self-management behavior of people with MS. [6,22] added that the majority of MS patients who suffering from fatigue are young adult on their most productive years of life, it can be severe, tends to persist over time and it can lead to MS complications or disability after long period of time. Furthermore [46,47] explained that living with a chronic disease like MS needs to control the disease and limit its progression on early stage , in which young MS individuals play an important role in self-management of the daily effects of the disease on their lives through early control strategy such as self management and changing lifestyle to adjust it.…”
Section: Discussionmentioning
confidence: 99%
“…11 Qatif Central Hospital, Qatif, Saudi Arabia. 12 King Faisal Specialist Hospital & Research Center, Jeddah, Saudi Arabia. 13 Prince Sultan Military Medical City, Riyadh, Saudi Arabia.…”
Section: Fundingmentioning
confidence: 99%
“…Other environmental factors such as vitamin D levels, obesity, and certain early childhood exposure to infectious agents, smoking, and certain other modifiable risk factors are associated with increased risk of MS. [9] As per Kurtzke classification, prevalence of MS in the Gulf region is marked as low-risk zone, however recent data have shown marked increased in the prevalence of MS, nearly 31-55 MS per 100,0000 individuals [10]. The increased prevalence in the Gulf region could be associated with change in lifestyle conditions, vitamin D deficiency and parental consanguinity as reported by few studies [11,12]. However, the lack of a central MS registry and long term follow-up epidemiological studies, make it difficult to understand the actual prevalence and associated factors related to the increasing number of MS cases in the region.…”
Section: Introductionmentioning
confidence: 99%
“…(10) The increased prevalence in the Gulf region could be associated with change in lifestyle conditions, vitamin D deficiency and parental consanguinity as reported by few studies. (11,12) However, the lack of a central MS registry and long term follow-up epidemiological studies, make it difficult to understand the actual prevalence and associated factors related to the increasing number of MS cases in the region.…”
Section: Introductionmentioning
confidence: 99%